2016
DOI: 10.1590/00115258201682
|View full text |Cite
|
Sign up to set email alerts
|

As Relações Civis-Militares em Portugal: O Longo Processo para o Controle Civil e a Eficácia Militar

Abstract: RESUMO O artigo trata das relações entre civis e militares em Portugal usando um quadro analítico baseado em indicadores empíricos relativos a três dimensões: controle democrático por parte de civis, eficácia no desempenho de tarefas e missões, e eficiência. Apesar da crise econômica e da consequente falta de recursos do governo, esta análise se mostra positiva numa perspectiva comparada. Ademais da influência e dos incentivos de organizações internacionais, especificamente da OTAN, da União Europeia e das Naç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…The first assumption considers that the place and function of military institutions in society are determining factors for the stability of the State (Vieira 2004). This relationship was verified by Bruneau (2016) in the Portuguese case, as he found that not only the Portuguese military, but also civilians are directly influenced by internal political stability and by external actors, such as the North Atlantic Treaty Organization (NATO) and the European Union. Regarding institutionalization, he identified the General Staff of the Armed Forces and the joint military professional training as essential elements for the effectiveness of the Portuguese Armed Forces' actions, even in the midst of the economic crisis experienced by Portugal.…”
Section: Promotion Of a South American Defense Identitymentioning
confidence: 84%
See 1 more Smart Citation
“…The first assumption considers that the place and function of military institutions in society are determining factors for the stability of the State (Vieira 2004). This relationship was verified by Bruneau (2016) in the Portuguese case, as he found that not only the Portuguese military, but also civilians are directly influenced by internal political stability and by external actors, such as the North Atlantic Treaty Organization (NATO) and the European Union. Regarding institutionalization, he identified the General Staff of the Armed Forces and the joint military professional training as essential elements for the effectiveness of the Portuguese Armed Forces' actions, even in the midst of the economic crisis experienced by Portugal.…”
Section: Promotion Of a South American Defense Identitymentioning
confidence: 84%
“…Regarding effectiveness, Bruneau (2016) proposes three basic requirements for the Armed Forces to fulfill their missions, whether it be for external defense, homeland security or peace and humanitarian aid missions, for example: i) there must be a plan that can be called doctrine or strategy; ii) there must be structures and processes to formulate plans and execute them; and iii) there must be a commitment of resources, financial and personnel, to ensure the implementation of the plan.…”
Section: Promotion Of a South American Defense Identitymentioning
confidence: 99%
“…A educação profissional militar é considerada um pilar do controle civil democrático em todo o mundo. Torná-la parte de um sistema educacional sob supervisão civil é objetivo relevante, em particular para as democracias recentes (BRUNEAU, 2016). No Brasil, a autonomia entre os sistemas educacionais civis e militares é prevista constitucionalmente, e foi reafirmada no artigo 83 da Lei de Diretrizes e Bases para o Ensino (Lei 9394/96), que estabelece: "o ensino militar é regulado por lei específica, admitida a equivalência de estudos, de acordo com as normas fixadas pelos sistemas de ensino" (Brasil, 1996).…”
Section: Introductionunclassified
“…Military professional education is considered a pillar of democratic civilian control throughout the world. It is part of an education system under civilian supervision is a relevant objective, particularly for recent democracies (BRUNEAU, 2016). In Brazil, the autonomy between the civil and military education systems is constitutionally foreseen and was reaffirmed in article 83 of the Law of Directives and Bases for Teaching (Law 9394/96), which establishes: "military education is regulated by a specific law, admitting the equivalence of studies, according to the norms established by the education systems" (Brasil, 1996).…”
Section: Introductionmentioning
confidence: 99%